1997
DOI: 10.1002/(sici)1097-4547(19971115)50:4<549::aid-jnr6>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptors prevent nitric oxide‐induced programmed cell death

Abstract: Activation of metabotropic glutamate receptor (mGluR) subtypes can prevent neuronal injury through the signal transduction pathways of nitric oxide (NO). It is this link to NO free radical injury and subsequent DNA damage that is the most intriguing. We therefore examined whether neuronal protection through mGluR activation was dependent on the molecular mechanisms of programmed cell death (PCD). The NO generators sodium nitroprusside and 3-morpholino-sydnonimine were administered to induce NO toxicity in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…65 The protective effects of mGluRII activation are not limited to experimental Parkinsonism but include protection against ischemia, 66 excitotoxic damage 67 and nitric oxide-induced programmed cell death. 68 Taken together, it is possible to suggest that the modulation of glutamatergic systems might be of clinical relevance by virtue, at least in part, of increased BDNF production implying that the neurotrophin might actively participate in affording neuroprotection in PD.…”
Section: Glutamatergic Drugsmentioning
confidence: 99%
“…65 The protective effects of mGluRII activation are not limited to experimental Parkinsonism but include protection against ischemia, 66 excitotoxic damage 67 and nitric oxide-induced programmed cell death. 68 Taken together, it is possible to suggest that the modulation of glutamatergic systems might be of clinical relevance by virtue, at least in part, of increased BDNF production implying that the neurotrophin might actively participate in affording neuroprotection in PD.…”
Section: Glutamatergic Drugsmentioning
confidence: 99%
“…Current interest has focused on the protective role of the mGluR system in the nervous system. mGluR activation prevents and, in some cases, reverses genomic DNA degradation [236], modulates endonuclease activation [237], and maintains cellular membrane asymmetry [235]. Cytoprotection by the mGluR system is believed to act at or below the level of free radical generation and oxidative stress [143,192,236].…”
Section: Modulation Of the Metabotropic Glutamate Systemmentioning
confidence: 99%
“…mGluR activation prevents and, in some cases, reverses genomic DNA degradation [236], modulates endonuclease activation [237], and maintains cellular membrane asymmetry [235]. Cytoprotection by the mGluR system is believed to act at or below the level of free radical generation and oxidative stress [143,192,236]. More recent work has suggested that mGluR offers similar protective capacity to the vascular system by preventing endothelial cell DNA degradation, caspase activity, and inhibiting a thrombotic state through the maintenance of membrane asymmetry [125,124,142].…”
Section: Modulation Of the Metabotropic Glutamate Systemmentioning
confidence: 99%
“…Current interest has focused on the protective role of the mGluR system in the nervous system. mGluR activation prevents, and in some cases, reverses genomic DNA degradation (Vincent, AM et al, 1997), modulates endonuclease activation , and maintains cellular membrane asymmetry . Cytoprotection by the mGluR system is believed to act at or below the level of free radical generation and oxidative stress (Maiese, K et al, 1996, Sagara, Y and Schubert, D, 1998, Vincent, AM et al, 1997.…”
Section: The Metabotropic Glutamate System During Neurodegenerationmentioning
confidence: 99%
“…mGluR activation prevents, and in some cases, reverses genomic DNA degradation (Vincent, AM et al, 1997), modulates endonuclease activation , and maintains cellular membrane asymmetry . Cytoprotection by the mGluR system is believed to act at or below the level of free radical generation and oxidative stress (Maiese, K et al, 1996, Sagara, Y and Schubert, D, 1998, Vincent, AM et al, 1997. More recent work has suggested that the mGluR offers similar protective capacity to the vascular system by preventing endothelial cell DNA degradation, caspase activity, and inhibiting a thrombotic state through the maintenance of membrane asymmetry (Lin, S-H et al, 2002, Lin, SH et al, 2001.…”
Section: The Metabotropic Glutamate System During Neurodegenerationmentioning
confidence: 99%